134 High incidence of acute circumflex artery injury following mitral isthmus ablation. (22nd September 2015) - Wong, K C K; Lim, C S; Sadarmin, P P; de Bono, J; Qureshi, Norman; Jones, M; Bashir, Y; Rajappan, K; Betts, T R
Abstract : Background: Mitral isthmus ablation is technically challenging and often requires epicardial ablation in the coronary sinus (CS) for success. The circumflex artery lies in close proximity to the CS and mitral annulus and may potentially be injured during radiofrequency ablation. This study investigates the incidence of coronary artery injury following mitral isthmus ablation. Methods: This is a single-centre, prospective study of 34 patients who underwent mitral isthmus ablation for atrial fibrillation (AF) and/or atrial tachycardia. Irrigation ablation catheters were used with the following settings: endocardial surface (max power: 40/50 W at the annular end; max temperature: 48°C; flow rate: 20 mls/min); CS (max power: 25/30 W; max temperature: 48°C; flow rate: 20 mls/min). Left coronary angiography was performed pre- and post-ablation. The angiograms were analysed off-line by an independent interventional cardiologist blinded to the ablation procedure. Quantitative Coronary Angiography (QCA) was performed for proximal, mid and distal circumflex artery (Cx), the obtuse marginal branch (OM) and the proximal left anterior descending artery (LAD). Results: The mean age is 57±11 years, 73% are males, 81% have persistent AF, 35% have structural heart disease and mean left atrial size is 44 mm. Successful mitral isthmus block was achieved in 88% and CS ablation was performed in 68%. The mean ablation times were 686 s (total), 508 s (endocardial) and 170 s (CS). The mean diameters of the vessels are presented in Abstract 134 table 1 . Seven out of 34 patients (21%) had mild atheromatous disease at the start. Ten patients (29%) had new angiographic changes following ablation: three had distal occlusion of very small distal Cx; five had stenosis of mid Cx (40–85% stenosis); One had stenosis of mid Cx (60%) and proximal OM (40%); One had stenosis of proximal Cx (25%) and proximal OM (35%). The significant stenoses resolved with intracoronary Glycerin Trinitrate (GTN). Hence, they were likely to represent spasm. Small Cx (<1.5 cm) was associated with a higher risk of injury (50% vs 22%, p<0.05). All significant stenoses were associated with CS ablation. Two cases of small distal Cx occlusion occurred in patients who had endocardial ablation only (40 W). Patients who had Cx artery injury tended to have longer mean ablation times but this did not reach significance (total: 818 s vs 627 s; CS: 240 s vs 139 s; endocardial: 578 s vs 477 s). These patients did not report any clinical symptoms. Mild stenosis 1 prox Cx, 1 prox OM Moderate stenosis 4 mid Cx, 1 prox OM Severe stenosis 2 mid Cx Occlusion 3 distal Cx Conclusions: Twenty nine per cent of patients had acute angiographic changes following mitral isthmus ablation. In many cases, they represent coronary spasm. These did not result in clinical symptoms. Further studies are needed to investigate the long term outcome of these patients.